PARENTS` EXPERIENCES EDUCATING THEIR CHILDREN WITH A DISABILITY ENROLLED IN HOMESCHOOLING IN KOSSHY - Mukashev, Kairat (Nazarbayev University Graduate School of Education, 2022)
There are several special education provisions for children with disabilities in Kazakhstan, including home education which is characterized as an alternative model of education to mainstream and private educational organizations. Hence, parents become the central figure in managing the home education process as the meeting special needs of children depends on their knowledge and experience. The present study explores parents` experiences in home educating a child with special needs in Kosshy. This case study applied a qualitative approach, the data was collected through face-to-face interviews with six parents about their experiences in home educating a child with disabilities. The findings demonstrate that the diagnosis of a child`s special needs brings negative psychological, social and financial impacts on parents` life. Moreover, the findings of the present study illustrate the problems parents experience in home-educating their children in one region of Kazakhstan including a lack of teachers` skills, issues related to a child's diagnosis, and certain challenges parents face such as providing a separate study room for a child. Furthermore, the support parents receive is limited and scarce and most parents shared that they are not provided with an opportunity to be involved in the decisions related to their child's education and get rare opportunities to visit non-academic activities at school. This indicates that the home education process for children with special needs in Kazakhstan may not be well organized in some regions of the country due to the lack of a clear system, guidelines for schools, teachers, and information for parents. Hence, these findings suggest that parents need adequate support and active involvement in the home education process to meet the needs of a child effectively which may be possible through a close partnership between parents, school and community with shared goals and responsibilities.
Keywords: Type of access: Open Access; children with disabilities; special education provision; Kazakhstan